Vzpostavljanje diplomatskih organizacij novih majhnih držav - Jazbec, Milan (Teorija in praksa, 1998)
While establishing their diplomatic organisations new small states have to solve a complex task. Its most important elements are sociological, organisational and linguistic ones. Limited human resources as a characteristic of small populations could strengthen the tendency of establishing the professional diplomacy. This has an important influence on the organisational model, which has to ensure functional and flexible providing of foreign policy information. Within this context the Slovene language with its specific terminology has an opportunity to function also as a diplomatic language.
Keywords: diplomacija; diplomacy; diplomatski odnosi; male države; mednarodni odnosi; terminologija; terminology; slovenska diplomacija